Plant extracts for drug development: Is it economical? - Binafsha Manzoor Syed (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
Plants have been in use for medicinal purposes for centuries. A number of drugs have been developed from plant extracts and are currently in clinical practice. There are still a number of diseases where there is no specific treatment available such as dengue fever or only synthetic molecules are there with a number of side effects. Thus considering plants for development of new drugs would be a viable option, however it’s a time consuming and rigorious process. However when compared to the synthetic molecules the initial cost incurred upon extraction and identification of the molecules from plant is much lower, the remaining clinical trial and quality control checks remain the same.